Immobilisation of microperoxidase-11 into layered MoO3 for applications of enzymatic conversion. (September 2019) - Wang, Yichao; Zhang, Shuang; Haque, Enamul; Zhang, Bao Yue; Ou, Jian Zhen; Liu, Jing; Liu, Zhongqing; Li, Yongxiang; Gao, Weimin; Haque, Farjana; Xu, Kai; Wang, Hongbin; et al.
Graphical abstract: Highlights: A hybrid material of layered MoO3 and microperoxidase-11 (MP-11) was successfully synthesised by a self-assembly technique through a covalent interaction. A covalent Mo-S bonding was formed during the immobilisation of MP-11 into MoO3 . There is a facile charge transfer from MP-11 to MoO3 upon light excitation. Improved enzymatic conversions were observed in the hybrid of MoO3 and MP-11, due to the synergetic effects of two entities. Abstract: Microperoxidase-11 (MP-11) has been widely used in enzymatic reactions. Further improvement of its performance requires a better charge transfer and more exposure of its active site in the enzymatic conversions, which can be achieved by immobilisation of MP-11 into functional materials. However, conventional immobilisation techniques always suffer from non-specific and uncontrolled weak interactions and energy level of two entities in the hybrid is not perfectly matched, thus resulting in limited improvement of the system. In this work, a hybrid material of layered MoO3 and MP-11 was synthesised by a self-assembly technique through a covalent interaction. Physicochemical characterisation indicated that there is a charge transfer from MP-11 to MoO3 and a covalent bond is formed in the hybrid. A notable enhancement of biocatalysis and photocurrent conversion were observed in the studies, which are due to a synergistic effect and band alignment of the two entities in the hybrid. The superior combined properties provide a great opportunity for developing high performance enzymatic conversion systems.